Driving performance through leadership and culture: The job satisfaction connection - Nabila, Sarah Jauzaa; Setyawati, Christina Yanita; Gunawan, Ni Luh Kadek Mudarani Andriani (Institute of Accounting Research and Novation (IARN), 2025)
The high employee turnover over several years at PT Jatianom Indah Farm has had an impact on the organization's ability to optimize sales so that it can maintain its position in the market. Therefore, companies need to review employee satisfaction which is influenced by the leadership style and organizational culture within the company. Employee satisfaction is also influenced by employee performanceThis study aims to examine the influence of leadership style and organizational culture on employee performance, with employee job satisfaction as a mediating variable. Using a quantitative approach, data were collected through a Likert-scale questionnaire with a 100% response rate from 110 participants. Structural Equation Modeling (SEM) was employed to analyze the outer model, inner model, and hypotheses. The results show that leadership style and organizational culture significantly affect employee performance, and both variables also significantly influence employee job satisfaction. Furthermore, employee job satisfaction significantly impacts employee performance and mediates the relationship between leadership style and employee performance. However, employee job satisfaction does not mediate the relationship between organizational culture and employee performance. Improving employee satisfaction is expected to reduce employee turnover within the company.